Pengaruh Pendekatan Saintifik Terhadap Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Raito, Raito; Tirayanti, Gina (STAI Al-Musaddadiyah Garut, 2023)
Critical thinking ability refers to the process through which students systematically dissect problems, accurately identify and distinguish issues with precision. The challenges observed in the research setting include students' delays in responding to information during the learning process, a lack of reading engagement, and some students remaining passive. The scientific approach is a learning methodology that offers students opportunities to explore and elaborate on the materials being studied. Consequently, this approach can enhance students' critical thinking abilities. This study aims to describe the impact of the scientific approach on students' critical thinking abilities in Islamic Religious Education (PAI) classes. The objective is to ascertain the extent of the relationship between the scientific approach and the students' critical thinking skills. The research method employed is descriptive quantitative correlational. Data collection techniques include observation, interviews, questionnaires, and documentation studies. Data analysis is conducted through statistical data processing. The findings indicate that the implementation of the scientific approach in learning received an average rating of 4.31, categorized as very good. Meanwhile, the improvement in students' critical thinking abilities achieved an average rating of 4.37, also categorized as very good. Statistical tests reveal that the scientific approach accounts for 52.75% of the variation in students' critical thinking abilities, while the remaining 47.25% is influenced by other factors not included in this study. Keywords: Scientific Approach; Critical Thinking Ability; Islamic Religious Education.